HUBUNGAN FLEKSIBILITAS KOGNITIF DAN EFIKASI DIRI DENGAN KOMPETENSI KEWIRAUSAHAAN MAHASISWA CALON GURU PENDIDIKAN TEKNIK FKIP UNS - Sri Handayani; Muhammad Akhyar; Indah Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
This study aims to determine whether there is a relationship between cognitive flexibility and self-efficacy with the entrepreneurial competence of prospective teacher students, namely a case study of Vocational Engineering Education students. This research was conducted using a quantitative approach, cognitive flexibility and self-efficacy as independent variables, entrepreneurial competence as the dependent variable. The population in this study were active students of the Sebelas Maret University majoring Vocational Engineering Education class 2018-2021. The total population is 921 students who consist of 315 students of Mechanical Engineering Education Study Program, Building Engineering Education as many as 297 students, and Information and Computer Engineering Education as many as 309 students. The researcher used the Stratified Random Sampling method in determining the sample size. The technique used to collect data using a Likert scale instrument. During the data collection process, the Sub-competences of Entrepreneurial Competency and Underlying Behavioral Indicators were used to measure the entrepreneurial competencies of prospective teacher students, Cognitive Flexibility Inventory (CFI) to measure the level of cognitive flexibility, and the General Self-Efficacy Scale (GSE) to measure the level of self-efficacy. The analytical method used is multiple linear regression analysis. The results of this study indicate that there is a positive relationship between cognitive flexibility and self-efficacy with entrepreneurial competence (R=.736, R2=.542, p=.000). Therefore, it can be said that the entrepreneurial competence of prospective teacher students can be improved through cognitive flexibility and self-efficacy beliefs.